2018
DOI: 10.20517/2394-4722.2018.39
|View full text |Cite
|
Sign up to set email alerts
|

Two sides to colon cancer: mice mimic human anatomical region disparity in colon cancer development and progression

Abstract: Aim: Strong evidence reveals important differences between cancers in the proximal vs. distal colon. Animal models of metastatic colon cancer are available but with varying degrees of reproducibility and several important limitations. We explored whether there were regional differences in the location of murine colon cancers and assessed the utility of murine models to explore the biological basis for such differences. Methods: We re-analyzed data from our previous studies to assess the regional distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…These multidirectional interactions between the gut microbiome, CRC cells, and enteric neurons are likely to promote cancer progression; stronger evidence awaits better experimental models (153). Because differences in immune, epithelial, and neural cell functions and microbial diversity in one region of the colon may impact cancer development and progression at other sites, purely reductionist approaches to explore links between the microbiome, ENS, and neoplasia may be misleading (157,158).…”
Section: R E V I E W S E R I E S : G U T-b R a I N A X I Smentioning
confidence: 99%
See 1 more Smart Citation
“…These multidirectional interactions between the gut microbiome, CRC cells, and enteric neurons are likely to promote cancer progression; stronger evidence awaits better experimental models (153). Because differences in immune, epithelial, and neural cell functions and microbial diversity in one region of the colon may impact cancer development and progression at other sites, purely reductionist approaches to explore links between the microbiome, ENS, and neoplasia may be misleading (157,158).…”
Section: R E V I E W S E R I E S : G U T-b R a I N A X I Smentioning
confidence: 99%
“…More cynically, these models represent only a change in culture medium from in vitro solutions to live organisms; xenograft experiments almost uniformly mirror in vitro findings without offering novel mechanistic insights, providing only an incremental advance and limited validation of in vitro findings. Orthotopic xenografts may more faithfully replicate human cancer progression and metastasis, e.g., human colon cancer cells implanted in the mouse sigmoid colon (157,184). Patient-derived xenografts (PDXs) can provide real-time information to develop cancer-specific treatment (176).…”
Section: R E V I E W S E R I E S : G U T-b R a I N A X I Smentioning
confidence: 99%
“…M 3 R is overexpressed in colon cancer, a finding that correlates with poor prognostic features including increased tumor burden, invasion, and metastasis [ 62 , 101 , 102 ]. M 3 R signal transduction, via the EGFR/ERK and PKC/p38 MAPK pathways, results in the induction and release of selected matrix metalloproteinases (MMP1, MMP7, and MMP10), collagenases that facilitate cell invasion by breaking down the extracellular matrix [ 103 , 104 ]. Additional studies showed that ACh-induced MMP1 expression and colon cancer cell invasion can be abolished by pre-treatment with inhibitors of muscarinic receptor or MMP1 activation [ 12 , 105 ].…”
Section: Differential Role Of Muscarinic Receptor Subtype Activation In Gi Cancersmentioning
confidence: 99%
“…Suppressing M 3 R expression using RNA interference attenuated bile acid-induced expression of markers of colon cancer stem cells. It appears plausible that M 3 R activation by exposure to luminal bile acids may explain, at least in part, the increased incidence of colon cancer in individuals who consume diets high in saturated fats that are known to increase levels of secondary bile acids in the stool [ 42 , 103 , 109 , 110 ].…”
Section: Differential Role Of Muscarinic Receptor Subtype Activation In Gi Cancersmentioning
confidence: 99%